Arrhythmias in children undergoing orthotopic heart transplantation - Doğan, Eser; Ergin, Fırat; Beyter, Mehmet B.; Kaşıkçı, Gülçin K.; Ön, Şeyma Ş.; Ay, Oğuzhan; Levent, Reşit E.; Engin, Çağatay; Ülger, Zülal (Frontiers in Cardiovascular Medicine, 2024)
Introduction Heart transplantation (HT) is the only treatment option in children with heart failure secondary to cardiomyopathies and non-reparable congenital heart diseases. Methods We performed a retrospective clinical data review of all consecutive pediatric patients (aged 2–18 years) who underwent orthotopic HT for advanced heart failure at our institution between January 2007 and January 2023. Clinical, procedural, and follow-up data were collected and comprehensively analyzed. Results We identified 27 children (66.7% males) with a median age of 15 years (IQR: 7–16) and a median weight of 45 kg (IQR: 22–66) at the time of the intervention. 24 patients (88.8%) were diagnosed with dilated cardiomyopathy, 2 (7.4%) with restrictive cardiomyopathy, and 1 (3.7%) with hypertrophic cardiomyopathy. On a median follow-up of 35.07 months (IQR: 13.13–111.87), arrhythmias were detected in 9 (33%) patients. Three patients developed symptomatic sinus node dysfunction at 18, 25, and 38 days and received permanent pacemakers. One patient developed a complete AV block during acute rejection at 76 months and received a temporary pacemaker. Two patients developed chronic sinus tachycardia at 4 and 16 months and were treated with Beta-blockers after eliminating all causes of sinus tachycardia. One patient developed a complete right bundle branch block at 12 months. One patient developed ventricular extrasystole at 10 months and was found to have grade 2 rejection. An Atrial extrasystole was detected in one patient at 96 months. We did not identify significant risk factors for arrhythmias post-HT. Discussion After pediatric HT, early-onset rhythm disturbances, often attributed to surgery-related issues such as sinus node dysfunction, may necessitate invasive treatments like permanent pacemaker therapy. Close monitoring post-transplantation is crucial, and routine follow-up with Holter ECG is necessary to identify potential rhythm disorders even in the absence of symptoms. Rhythm disturbances that develop during follow-up can serve as early indicators of graft rejection and should be carefully evaluated.